The level of exposure and awareness of Ilonggo audience towards TV political advertisement. - Esclares, Kristianly Hazel
The study "The level of Exposure and Awareness of Audience Towards TV Political Advertisements" provides in-depth comprehension on how the exposure to TV Product and Advocacy Advertisements endorsed by Politicians affect the level of knowledge of the audience. It also provides information about how media shapes and influences the opinion and ideas of the audience. The results of the study show that the more the audience is exposed to the TV Political Advertisements, the higher their awareness is. The study covered 14 barangays in Iloilo City Proper with a total of 210 respondents.